MARKETING MIX FACTORS AFFECTING CUSTOMERS' PURCHASING BEHAVIOR OF SECOND - HAND DOLLS THROUGH ONLINE CHANNELS - Wangnai, Thidarut; Pongsamran, Sutham; Thanphan, Ingorn (Journal of MCU Nakhondhat, 2024)
This research aims to study 1) the marketing mix factors, 2) the behavior of customers in purchasing second-hand dolls via online channels, 3) comparing customers purchasing behavior of second-hand dolls via online channels classified by personal information, and 4) the marketing mix factors that affect customers' behavior of purchasing second-hand dolls through online channels. The study is a quantitative research tool using a questionnaire. Calculated by W.G. Cochran's formula and a sample of 400 was people who had previously purchased second - hand dolls online and processed using statistical percentage, mean, Chi-square, and Multiple Regression Analysis. The results of the study found that most the behavior of customers buy medium-sized licensed cartoons doll, mainly considering the type/style of the doll. Choose to buy by self - decision, according to preferences/accumulation via Facebook, through the reviews, purchase on average 3.5 times per year, with an average cost of 526.70 baht per time. The difference in personnel information gender, age, levels of education, occupation and income influences the difference customers' behavior in purchasing second-hand dolls online. Marketing mix factors are at a high level. Regarding prices, distribution channels, and promotion, they influenced customers' purchasing of second-hand dolls online with a significance of 0.01 level. The study recommends that products be clean, safe, and not harmful to users. It is outstanding and unique. Product listings should include accurate product information, and shows a clear selling price. There are many payment channels and quick and on - time delivery. Shipping costs are reasonable. Knowledgeable salespeople know about the products. Able to answer customer questions clearly. There should increase distribution channels. Including promote sales.